Comparison of two methods to assess variability of platelet response to anti-platelet therapies in patients with acute coronary syndrome undergoing angioplasty - Ahnadi, Charaf E.; Boughrassa, Faiza F.; Chapman-Montgomery, E. Sabrinah; Poisson, Véronique; Gervais, André; Okrongly, David; Grant, Andrew M. (Thrombosis and Haemostasis, 2004)
The study investigated the clinical usefulness of a new method to evaluate platelet activation and the variability of platelet response to anti-platelet therapy in patients undergoing percutaneous transluminal coronary angioplasty (PTCA). Platelet activation was assessed in parallel by a new method for platelet density measurements (MPC, Mean Platelet Component Concentration), on the automated ADVIA 120 Hematology System and by the classic measurement of P-selectin (CD62P) expression, on a fluorescence flow cytometer. Patients received a loading dose of clopidogrel (300 mg; n = 29) or a bolus of abciximab (0.25 mg/kg; n = 15). Blood samples were collected before (baseline) and at different times after PTCA and antiplatelet drugs administration. Our data showed a close inverse correlation between the change in MPC and the CD62P fluorescence surface marker expression (r = 0.776, P<0.0001). Individual platelet activation determinations in patients receiving either clopidogrel or abciximab showed a variation in platelet activation as assayed by MPC and CD62P expression. Patients were characterized as having either high platelet activity upon admission and positive response to treatment or no detectable platelet activation before or after treatment. This study demonstrates the heterogeneity of platelet activation states in ACS patients undergoing coronary angioplasty. The present work also illustrates the potential use of the MPC parameter, generated on an automated hematology system, to define high risk patients and to monitor the variability of platelet response to anti-platelet therapies.
Keywords: Platelets activation; anti-platelet drugs; ADVIA 120; CD62P